Pembentukan Makna Cinta melalui Film Puspa Indah Taman Hati 2023 - Arshimny, Hatfina Izzati; Wempi, Chrisdina (Wardah, 2026)
This research aims to explore the meaning-making of love within the film Puspa Indah Taman Hati (2023) from the perspective of Generation Z. Using a descriptive qualitative approach, data were collected through Focus Group Discussions (FGD) with seven participants in Greater Jakarta and in-depth interviews with four film industry experts. The novelty of this research lies in the triangulation analysis that connects the industrial intervention in adapting a classic intellectual property with the meaning negotiation of modern audiences. The findings reveal that the film reconstructs classic romanticism by injecting contemporary egalitarian values. Textually, the visual narrative accentuates reciprocal relational validation. Crucially, the research demonstrates that Generation Z operates as active audiences who critically deconstruct the historical glorification of asymmetrical sacrifices. They reject toxic romanticism and redefine love as an egalitarian partnership upholding transparent communication and female autonomy. In conclusion, the discourse of love among young audiences has fundamentally shifted from tragic idealism toward a rational, mindful, and equitable affective relationship.